PENERAPAN PEMBELAJARAN TWO STAY TWO STRAY DAN PROBING PROMPTING TERHADAP KEMAMPUAN BERFIKIR SPASIAL SISWA - Islami, Nur Intan; Tampubolon, Budiman; Anasi, Putri Tipa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe purpose of this research is to analize the differerent of two stay two stray and probing prompting learning for spatial thinking skills in the XI grade studens ofÂ  SMA N 8 Pontianak. The research approach used a quantitative and an experiment method with quasi experiment form. The population in this research were students in the XI grade of SMA N 8 Pontianak 2019/2020 academic year. Data collection used multiple chioce test amounted to 30 questions and data analysis techniques used separated varians t-test. The results showed that spatial thinking skills of the first experimental class has an average value of 85,93, while the second experimental class has an average value of 76,32, gained Tarithmatic > Ttable, is 4,9>1,9934, which is means there are differences in the spatial thinking skills of students who apply two stay two stray and probing prompting learning in XI grade students ofÂ  SMA N 8 Pontianak.Keywords: Two Stay Two Stray, Probing Prompting, Spatial Thinking Skill